Cross-cultural roots of minority child development
1 online resource (xxiv, 425 pages)
Keywords: "Cross-Cultural Roots of Minority Child Development was the first volume to analyze minority child development by comparing minority children to children in their ancestral countries, rather than to children in the host culture. It was a ground-breaking volume that not only offered an historical reconstruction of the cross-cultural roots of minority child development, but a new cultural-historical approach to developmental psychology as well. It was also one of the best attempts to develop guidelines for building models of development that are multicultural in perspective, thus challenging scholars across the behavioral sciences to give more credence to the impact of culture on development and socialization in their respective fields of work. A true classic, Cross-Cultural Roots of Minority Child Development will remain an essential resource for any scholar who is interested in minority child development and engages in cross-cultural research and multidisciplinary methodologies"--